Development of individual living space consumption between 1978 and 2013: determinants and transformative potential - Weber, Ines (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
In Germany, the trend towards increasing per capita living space continues. The achievement of the reduction targets with regard to the energy consumption of residential buildings is thereby counteracted. While the structural drivers behind this development – for example shifts in preferences, increasing prosperity and demographic change – have been well-researched individually, their proportional quantitative power of influence remains uncertain. Based on data from the Income and Expenditure Survey (EVS) for the time period of 1978 to 2013, this paper examines to what extent the development of housing consumption in Germany can be explained by socioeconomic and demographic changes over time. The results of a decomposition analysis show that demographic changes, in particular the reduction of the average household size, are the main responsible drivers for the increase in living space consumption per capita. This development is accompanied by rising housing costs, which increasingly burden all income groups, but especially poorer households. In recent years, the housing cost burden dampened a further expansion of living space consumption. In addition, an imbalance between housing supply and demand can be identified on the local level. This could be reduced by building smaller homes, rebuilding existing homes and encouraging the elderly in oversized homes to relocate. For this purpose, regulatory measures and/or incentive mechanisms would have to be implemented.